Clinical characteristics of pertussis in infants and risk factors for respiratory support - Cui Liru; Wang Jing; Bi Jing; Zhang Yu; Tian Jian; Jiang Min (Annals of Medicine)
Objective This study aims to analyze the clinical characteristics, treatment outcomes, and risk factors associated with respiratory support in infants hospitalized with pertussis.Patients and methods We retrospectively analyzed the clinical data of 0–1-year-old pertussis patients admitted to Baoding Hospital of Beijing Children's Hospital affiliated with Capital Medical University from January 2022 to May 2024. SPSS27.0 statistical software was used to analyze the differences in data among different groups of children with pertussis and to summarize their clinical characteristics. A multiple logistic regression model was used to analyze the clinical risk factors of the respiratory support group.Results We enrolled 233 hospitalized children with pertussis. Children requiring respiratory support had lower vaccination rates and higher incidences of cyanosis, wheezing, and RSV infection. Logistic regression identified age, cyanosis after coughing, and IVIG use as independent predictors of respiratory support. Age was an independent protective factor: older children were less likely to require respiratory support (OR = 0.151). Compared with children aged ≥3 months, children aged <3 months had a higher history of contact with cough patients, with symptoms such as cyanosis after coughing, white blood cell counts (WBCs) ≥20 × 109/L, lymphocyte percentage ≥60%, and increased RSV infection incidence. Rates of respiratory support, bronchoscopy treatment, IVIG, tracheal intubation, and exchange transfusion treatment increased (all p < 0.05).Conclusions Younger pertussis patients have more severe clinical manifestations, with significantly increased WBCs, and they are more likely to be infected with other viruses. Age is an independent protective factor, and the younger the patient, the more likely they are to require respiratory support. These findings highlight the need for early recognition and targeted interventions, particularly in younger infants with severe symptoms.